ANALISIS PENGARUH INVESTASI R & D TERHADAP RESIKO SISTEMATIS PADA PERUSAHAAN MANUFAKTUR - Farah Margaretha; Hartanti Hartanti (Universitas Trisakti, 2006)
Through invesment emiten and investor will get risk which cannot predicted. Where from the risk, there are risk able to lessen by diversified (unsystematic risk) and there also risk which cannot lessen (systematic risk). This research is doing to know how R&D invesment affect to systematic risk along with its component, there are business risk, DOL. DFL, and operating risk at manufacturing listed companies in Jakarta Stock Exchange during the six period of time (1999-2004). Hypothesis testing is used in this research. Independent variable which used in this research is R&D invesment, while dependent variables are systematic risk, business risk, DOL, DFL, and operating risk. This research is using analyse multivariat and regression and also data analysis SPSS data 11.5 program. The result of this research shows that R&D invesment have significant affect to systematic risk and its component, there are business risk, DOL, and operating risk. Manajerial implication in this research is destined to emiten, in expection of investing its capital is more paying attention to systematic risk, DOL, business risk, and operating risk to be obtained.